Query Processing on Gaming Consoles - Cui, Wei; Zhang, Qianxi; Camacho-Rodríguez, Jesús; Blanas, Spyros; Haynes, Brandon; Li, Yinan; Cheng, Peng; Ramamurthy, Ravishankar; Sen, Rathijit; Interlandi, Matteo (2023)
ACM Reference Format: Wei Cui, Qianxi Zhang, Spyros Blanas, Jesus Camacho-Rodriguez, Brandon Haynes,, Yinan Li, Ravi Ramamurthy, Peng Cheng, Rathijit Sen, Matteo Interlandi. 2023. Query Processing onGaming Consoles. In 19th International Workshop on Data Management on New Hardware (DaMoN ’23), June 18–23, 2023, Seattle, WA, USA. ACM, New York, NY, USA, 3 pages. https://doi.org/ 10.1145/3592980.3595313